IMPROVING STUDENTS’ READING COMPREHENSION THROUGH READING RESPONSE JOURNAL STRATEGY AT EIGHTH GRADE STUDENTS OF SMP N 1 BANJAR IN THE ACADEMIC YEAR 2015/2016 - ., Komang Tuti Irmawati; ., Ni Komang Arie Suwastini, S.Pd,M.Hum.; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini dikategorikan sebagai penelitian tindakan kelas yang telah dilaksanakan untuk meningkatkan pemahaman membaca siswa di kelas VIIIB di SMP N 1 Banjar tahun ajaran 2015/2016 melalui penerapan teknik Reading Response Journal. Penelitian ini telah dilaksanakan dalam dua siklus. Setiap siklus terdiri empat kegiatan utama yaitu, perencanaan, pelaksanaan, pengamatan dan refleksi. Untuk mengumpulkan data, ada tiga jenis instrument yang digunakan yaitu tes, angket, dan catatan harian peniliti. Data yang didapat dalam penelitian ini dianalisis secara kuantitatif dan kualitatif. Data yang diperoleh dalam pre-test dan post-test dianalisis secara kuantitatif, sedangkan data dari angket dan catatan harian peniliti dianalisis scera kualitatif. Berdasarkan dari hasil tes siswa dalam pre-test, hanya 12,5% siswa melewati KKM (kriteria kelulusan minimal). Tetapi dalam post-test I, hasilnya meningkat menjadi 57.5% siswa, dan terakhir pada post-test II, kriteria pencapaian sudah mencapai 87.5% siswa yang secara sukses melewati KKM (criteria kelulusan minimal). Dengan kata lain, kesuksesan dari penelitian juga berdasarkan dari hasil angket dan catatan harian peneliti yang menunjukkan sikap positif siswa terhadap penerapan dari teknik Reading Response Journal dalam kegiatan membaca siswa.Kata Kunci : pemahaman membaca, strategi Reading Response Journal, penelitian tindakan kelas, siswa kelas delapan This study was categorized as classroom action research which was done to improve the students’ reading comprehension at Class VIIIB in SMP N 1 Banjar in the academic year 2015/2016 through the implementation of Reading Response Journal strategy. This study was done in two cycles. Each cycle consisted of four main activities namely planning, action, observation and reflection. To collect the data, there were three kinds of instruments used namely tests, questionnaire, and researcher’s diary. The data obtained in this study were analyzed quantitatively and qualitatively. The data gained in pre-test and post-test were analyzed quantitatively, while the data from questionnaire and researcher’s diary were analyzed qualitatively. Based on the result of this study, it was found that the students’ reading comprehension in Class VIIIB in SMP N 1 Banjar had improved significantly. It was indicated by the result of students’ tests in which in pre-test, there were only 12.5% students passing the school passing grade. But in post-test I, the number increased into 57.7% students, and finally in post-test II, the criteria of success reached as 87.5% students could successfully passed the standard passing score. In addition, the success of the study was also based on the results of the questionnaire as well as the researcher’s diary which showed the students’ positive attitudes toward the implementation of the Reading Response Journal strategy in their reading activities.keyword : reading comprehension, Reading Response Journal strategy, classroom action research, eighth grade students.